Tidal turbine benchmarking project: stage I – steady flow experiments - Tucker Harvey, SW; Chen, X; Rowe, DT; McNaughton, J; Vogel, CR; Bhavsar, K; Allsop, T; Gilbert, J; Mullings, H; Stallard, T; Benson, I; Young, A; et al. (European Wave and Tidal Energy Conference, 2023)
The tidal turbine benchmarking project, funded by the UK's EPSRC and the Supergen ORE Hub, has conducted a large laboratory scale experiment on a highly instrumented 1.6m diameter tidal rotor. The turbine is instrumented for the measurement of spanwise distributions of flapwise and edgewise bending moments using strain gauges and a fibre Bragg optical system, as well as overall rotor torque and thrust. The turbine was tested in well-defined flow conditions, including grid-generated freestream turbulence, and was towed through the 12.2m wide, 5.4m deep long towing tank at Qinetiq’s Haslar facility. The turbine scale was such that blade Reynolds numbers were Re=3x10^5 and therefore post-critical, whilst turbine blockage was kept low at 3.1. In order to achieve higher levels of freestream turbulence a 2.4m by 2.4m turbulence grid was towed 5m upstream of the turbine. Measurements to characterise the grid generated turbulence were made at the rotor plane using an Acoustic Doppler Velocimeter and a five-hole pressure probe. An elevated turbulence of 3.1% with homogeneous flow speed across the rotor plane was achieved using the upstream turbulence grid. The experimental tests are well defined and repeatable, and provide relevant data for validating models intended for use in the design and analysis of full-scale turbines. This paper reports on the first experimental stage of the tidal benchmarking programme, including the design of the rotor and comparisons of the experimental results to blade resolved numerical simulations.